Developmental Features of Lexical Richness in English Writings by Chinese L3 Beginner Learners - Li, Xuelan; Zhang, Huiping (Frontiers in Psychology, 2021)
Lexical richness is considered as one of the most efficient methods for assessing writing proficiency and development. However, the developmental features of lexical richness in L3 writing remain relatively poorly understood compared with that of L2 writings. This study reports a cross-sectional corpus-based study that aims to explore the developmental features of lexical richness in L3 writings by Chinese beginner learners of English from the perspective of the dynamic usage-based approach. Specifically, this study compares samples of English writing by Chinese L3 secondary students (grades 7–12) aged 13–18 across three learning stages in terms of lexical sophistication, lexical diversity and lexical density. The writing samples were collected from the Writing Corpus of Chinese Ethnic Minority Beginner Learners as the Third Language (WCCMBL), and the sample sizes of the three stages remained almost the same. The results revealed that lexical richness was generally low in L3 beginner learners’ writing. Specifically, L3 beginner learners used fewer diverse words and lexical words, but used numerous high-frequency words in their writing. Additionally, lexical sophistication and lexical density yielded positive growth across the three learning stages, whereas lexical diversity developed non-linearly. These findings reveal a dynamic development of lexical richness in L3 writings, with each of the three measures developing unevenly. Drawing upon these findings, several suggestions for L3 vocabulary teaching are also proposed.